A Phosphorus(III)‐Mediated (4+1)‐Cycloaddition of 1, 2‐Dicarbonyls and Aza‐o‐Quinone Methides to Access 2, 3‐Dihydroindoles. Issue 12 (4th December 2019) - Eckert, Kaitlyn E.; Lepore, Antonio J.; Ashfeld, Brandon L.
Abstract: A (4+1)‐cycloaddition is reported between 1, 2‐dicarbonyls and aza‐ o ‐quinone methide precursors to access 2, 3‐dihydroindoles bearing a tetra‐substituted carbon center. The utilization of dioxyphospholenes as carbene surrogates provided dihydroindoles in 20–90 % yield, wherein the electronic nature of the dioxyphospholene impacts its role in the reaction. Abstract :